2017
DOI: 10.1175/jhm-d-16-0198.1
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparisons of Rainfall Estimates from TRMM and GPM Multisatellite Products over the Upper Mekong River Basin

Abstract: The aim of this study is to evaluate the accuracy of daily rainfall estimates based on the GPM level-3 final product derived from the IMERG algorithm (abbreviated as IMERG) and TRMM 3B42, version 7 (abbreviated as 3B42), in the upper Mekong River basin, a mountainous region in southwestern China. High-density rain gauges provide exceptional resources for ground validation of satellite rainfall estimates over this region. The performance of the two satellite rainfall products is evaluated during two rainy seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 62 publications
4
48
0
1
Order By: Relevance
“…Our study found that IMERG-F V05 and 3B42V7 have acceptable hydrological capabilities in the Chindwin River basin, with IMERG-F being slightly better than 3B42V7. Similar findings were reported in the Ganjiang River basin [45], Beijiang River basin [24], upper Mekong River basin [36], Mishui basin [25], Yellow River source region of China [44], and Amazon basin of Peru and Ecuador [48]. Yuan et al [47] employed the first hydrological evaluation research in the Chindwin River basin and found that IMERG-F V03 performs comparatively worse than 3B42V7 in daily streamflow simulations.…”
Section: Evaluation Of Hydrological Performance Of the Gpm-era Sppssupporting
confidence: 66%
See 1 more Smart Citation
“…Our study found that IMERG-F V05 and 3B42V7 have acceptable hydrological capabilities in the Chindwin River basin, with IMERG-F being slightly better than 3B42V7. Similar findings were reported in the Ganjiang River basin [45], Beijiang River basin [24], upper Mekong River basin [36], Mishui basin [25], Yellow River source region of China [44], and Amazon basin of Peru and Ecuador [48]. Yuan et al [47] employed the first hydrological evaluation research in the Chindwin River basin and found that IMERG-F V03 performs comparatively worse than 3B42V7 in daily streamflow simulations.…”
Section: Evaluation Of Hydrological Performance Of the Gpm-era Sppssupporting
confidence: 66%
“…techniques. However, most relevant studies [24,25,36,45,47,48,50] focused on assessing the hydrological utility of IMERG at daily or monthly time scales, while evaluations at sub-daily temporal scales have seldom been reported [44,46,49]. Furthermore, studies on the hydrological performance of all the "Early", "Late", and "Final" runs of IMERG are rare [24,25,50].…”
Section: Introductionmentioning
confidence: 99%
“…He et al . [] evaluated the accuracy of daily rainfall estimates using GPM IMERG and TRMM 3B42V7 products in Upper Mekong River basin and confirmed the outperformance of GPM IMERG over TRMM 3B42V7.…”
Section: Introductionmentioning
confidence: 99%
“…Prakash et al [2016] showed that IMERG product is superior in capturing heavy rainfall over India. He et al [2016] evaluated the accuracy of daily rainfall estimates using GPM IMERG and TRMM 3B42V7 products in Upper Mekong River basin and confirmed the outperformance of GPM IMERG over TRMM 3B42V7. Tong et al [2014b] compared five high-resolution reanalysis and satellite rainfall products, including the European Centre for Medium-range Weather Forecasts (ECMWF) reanalysis ERA-40, ERA-Interim, University of Washington data, Asian Precipitation-Highly Resolved Observational Data Integration Towards Evaluation's Water Resources, and TRMM 3B42V6, with Corrected-China Meteorological Administration data set over TP.…”
Section: Introductionmentioning
confidence: 99%
“…A number of global satellite rainfall products have been developed since the 1980s (He et al, 2016). The tropical rainfall measurement mission (TRMM), which housed the first-ever precipitation radar in space, is a collaborative effort between National Aeronautics and Space Administration (NASA) and the Japanese Aerospace Exploration Agency (JAXA) (Grecu & Bolvin, 2018).…”
Section: Introductionmentioning
confidence: 99%